1999
DOI: 10.21236/ada379831
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Plasma Aftertreatment for Simultaneous Control of NOx and Particulates

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate SUPPLEMENTARY NOTESNo copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…In this reaction system, when HC was added to the oxidizing gas containing NO, the NO oxidation to NO 2 was significantly enhanced and the NO conversion with HC increased three times compared with that without HC at 400 °C. This is consistent with the chemical kinetics model of Penetrante et al ,28 which suggested that NO oxidation occurs with the discharging nonthermal plasma containing HC by the following process: high energy electrons in the discharging nonthermal plasma generate O radicals, HC + O radicals → HO 2 radicals, NO + HO 2 radicals → NO 2 + OH radicals and that HC suppresses the reduction of NO 2 back to NO by O radicals and further oxidation of NO 2 to nitric acid by OH radicals by consuming these excess radicals. …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In this reaction system, when HC was added to the oxidizing gas containing NO, the NO oxidation to NO 2 was significantly enhanced and the NO conversion with HC increased three times compared with that without HC at 400 °C. This is consistent with the chemical kinetics model of Penetrante et al ,28 which suggested that NO oxidation occurs with the discharging nonthermal plasma containing HC by the following process: high energy electrons in the discharging nonthermal plasma generate O radicals, HC + O radicals → HO 2 radicals, NO + HO 2 radicals → NO 2 + OH radicals and that HC suppresses the reduction of NO 2 back to NO by O radicals and further oxidation of NO 2 to nitric acid by OH radicals by consuming these excess radicals. …”
Section: Resultssupporting
confidence: 92%
“…Above 300 °C, the NO conversions for both the plasma and the Pt/alumina approached the value of the thermal equilibrium condition. Similar phenomena have been reported by many researchers 17–21, 28. In this reaction system, when HC was added to the oxidizing gas containing NO, the NO oxidation to NO 2 was significantly enhanced and the NO conversion with HC increased three times compared with that without HC at 400 °C.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Additional aftertreatments are required to reduce 97% PM emission to the same PM emission level with that without EGR. Plasma technology has potential to reduce this excess PM emission (Chae et al, 2001; Chang, 1993; Chang et al, 1991; Dorai and Kushner, 1999; Dorai et al, 2000; Eliasson, 1991; Franick and Bykowski, 1994; Herling et al, 2000; Larkin et al, 1998; Lepperhoff et al, 1999; Liu et al, 1996; Matsui et al, 2001; Okubo and Yamamoto, 2002; Penetrante, 1993; Penetrante et al, 1999; Tamon et al, 1995, 1998; Thanyachotpaiboon et al, 1998; Thomas et al, 2000; Vercammen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Fast NH 3 −selective catalytic reduction (SCR) technology based on vanadium catalyst is an effective approach to improve NO x reduction efficiency under low temperature conditions of diesel engines. The precondition to achieve fast SCR is to oxidize part of NO to NO 2 in the upstream of the SCR reactor. It was found that in a nonthermal plasma process, the rate of NO oxidation is 2 orders of magnitude larger than that of SO 2 oxidation. Therefore, plasma oxidation of NO is more tolerant to sulfur content as compared to NO oxidation over noble catalysts. …”
Section: Introductionmentioning
confidence: 99%